Effects of minimum wage rate towards the unemployment rate - Islam, Rabiul; Abdul Ghani, Ahmad Bashawir; Zainal Abidin, Irwan Shah; Sundari, Abirama (ASERS Publishing House, 2017)
In Malaysia, the minimum wage policy was announced by the prime minister on 15 October 2010. It is also known as one of a government policies instruments vide New Economic Model (NEM) in order to transform economy in Malaysia from a middleincome to a high-income economy by the year 2020. The aim of this policy is to protect the right of the citizens who are earning especially low income per month and low skilled. The purpose of this paper is to investigate the effects of the minimum wage rate towards the national unemployment rate. It is done by conducting a very important process which is collecting data and information regarding the paper. It is then followed by preparing a full report on the related topic which is the effects of minimum wage rate towards the national unemployment rate. The data that been collected based on the problem statements and also based on the objective of the study related to the effects of minimum wage rate towards the national unemployment rate. This paper also conducted in order to examine the effect of the minimum wage rate on the rate of working adults as well as the preferences of the labours whether to work a part time or full time, which finally will reflect on the national unemployment rate.